Local communities, Marine Protected Areas and diving tourism in Cyclades - Avrami, Lydia; Demertzis, Nikos; Armenakis, Antonis (The Greek Review of Social Research, 2021)
This study aims to map and compare the perceptions and views of local stakeholders and interest groups of three Cyclades islands with different level of tourism development (Kythnos, Milos, Santorini) as for the newly designated Marine Protected Areas (MPA) and the development of diving tourism. In addition, the main factors that are expected to contribute or undermine the governance, the management and the ultimately effectiveness of MPAs in the above areas are explored. To this end, personal interviews were conducted with all local stakeholders, who are directly or indirectly involved in the management of MPAs and the development of diving tourism.The analysis demonstrates the substantial lack of information of local stakeholders and interest groups about MPAs. In addition, significant differences in their views are observed, which seem to be linked to the level of tourism development of each island, the structure of local economy and the local consultations conducted about the MPA designation in the past.